Assessment of mitral regurgitation in dogs: comparison of results of echocardiography with magnetic resonance imaging. (16th October 2015) - Sargent, J.; Connolly, D. J.; Watts, V.; Mõtsküla, P.; Volk, H. A.; Lamb, C. R.; Luis Fuentes, V.
Abstract: OBJECTIVES: Echocardiography is used routinely to assess mitral regurgitation severity, but echocardiographic measures of mitral regurgitation in dogs have not been compared with other quantitative methods. The study aim was to compare echocardiographic measures of mitral regurgitation with cardiac magnetic resonance imaging‐derived mitral regurgitant fraction in small‐breed dogs. METHODS: Dogs with myxomatous mitral valve disease scheduled for magnetic resonance imaging assessment of neurological disease were recruited. Correlations were tested between cardiac magnetic resonance imaging‐derived mitral regurgitant fraction and the following echocardiographic measures: vena contracta/aortic diameter, transmitral E‐wave velocity, amplitude of mitral prolapse/aortic diameter, diastolic left ventricular diameter:aortic diameter, left atrium:aortic diameter, mitral regurgitation jet area ratio and regurgitant fraction calculated using the proximal isovelocity surface area method. RESULTS: Measurement of cardiac magnetic resonance imaging‐derived mitral regurgitant fraction was attempted in 21 dogs. Twelve consecutive, complete studies were obtained and 10 dogs were included in the final analysis: vena contracta/aortic diameter (r = 0 · 89, p = 0 · 001) and E‐wave velocity (r = 0 · 86, p = 0 · 001) had the strongest correlations with cardiac magnetic resonance imaging‐derived mitral regurgitant fraction. E velocity had superior repeatability and could be measured in all dogs. The presence of multiple jets precluded vena contracta/aortic diameter measurement in one dog. CLINICAL SIGNIFICANCE: Measurement of cardiac magnetic resonance imaging‐derived mitral regurgitant fraction is feasible but technically demanding. The echocardiographic measures that correlated most closely with cardiac magnetic resonance imaging‐derived mitral regurgitant fraction were vena contracta/aortic diameter and E‐wave velocity.